The Relation of Parental Emotion Regulation to Child Autism Spectrum Disorder Core Symptoms: The Moderating Role of Child Cardiac Vagal Activity - Hu, Xiaoyi; Han, Zhuo Rachel; Wang, Hui; Hu, Yannan; Wang, Qiandong; Feng, Shuyuan; Yi, Li (Frontiers in Psychology, 2018)
This study investigated the role of parental emotion regulation on children’s core symptoms in families of children with autism spectrum disorders (ASD) in middle childhood; the study also explored whether children’s physiological emotion regulation (ER) functioning served as a risk or protective factor with respect to parental relationships. Thirty-one Chinese children with ASD (age 6-11) and their primary caregivers participated in this study. Parental emotion regulation and child ASD symptoms were collected via questionnaire from parents. Child cardiac vagal activity (derived from heart rate variability) was measured at rest and during a parent-child interaction task. Using moderation analysis, the results showed that parental emotion regulation was not directly associated with children’s core ASD symptoms; rather, it interacted significantly with children’s resting cardiac vagal activity, but not task-related changes of cardiac vagal activity, to exert an impact on children’s core ASD symptoms. Specifically, our findings suggest that parents’ difficulties with their own emotion regulation significantly impacted their children’s core ASD symptoms only for the children who showed blunted resting cardiac vagal activity. Implications for the future measurement of emotion regulation in the family context and future directions for intervention are discussed.